Toxic Masculinity in the Sadfishing Phenomenon within the #LakiLakiTidakBercerita Hashtag: A Netnographic Study of TikTok Content from the Account @bimbluess - Fitriyani, Nurul; Sadono, Teguh Priyo; Palupi, Merry Fridha Tri (Indonesian Journal Publisher, 2025)
Toxic masculinity is a form of gender injustice reflected through labeling and stereotypes toward men, especially when they attempt to express emotional vulnerability. This study explores how toxic masculinity is manifested in the sadfishing phenomenon on TikTok, particularly through the hashtag #LakiLakiTidakBercerita and user comments on the account @bimbluess. The phenomenon highlights a paradox in which men’s emotional openness is often met with responses that reinforce hegemonic masculinity norms. Using a qualitative approach through netnographic methods, this research analyzes digital user interactions as part of participatory media culture. The study is framed by standpoint theory and the concept of hegemonic masculinity to understand how gendered power structures operate in digital spaces. The findings reveal five key themes: (1) toxic masculinity as a generational emotional wound, (2) internalized masculine values as social consciousness, (3) fear of vulnerability and masculine performativity, (4) emotional self-sabotage, and (5) the burden of productivity seen as male destiny. These dynamics show how digital platforms can both challenge and reproduce gender norms.